Mitral Valve Regurgitation in two Thoroughbred Stallions - Pinar Orhan (Sciendo, 2016)
Mitral valve (MV) disease is the most important valvular condition affecting athletic performance in horses. Twenty and 22 years old Thoroughbred Stallions used for breeding had suffered from increased respiratory and heart rate, poor performance and incomplete ejaculate release during covering, since three months ago. Cardiac examination projected irregular cardiac rhythm after a halt and an early-mid-systolic murmur.